EDUKASI PENGGUNAAN KOSMETIK YANG AMAN TANPA BAHAN KIMIA BERBAHAYA TERHADAP SISWA SMA/K DI KABUPATEN KARAWANG - Nia Yuniarsih; Farhamzah, Farhamzah; Anggun Hari K; Himya H; Maulana Yusuf A; Sudrajat Sugiharta; Iin Lidia P. M (Bajang Institute, 2024)
Lifestyles are increasingly modern and people, especially teenagers, are starting to pay attention to the aesthetics of their skin, so they are competing to use various kinds of cosmetics that can support self-confidence, especially among teenagers. Almost all teenagers use their money for beauty maintenance needs by buying based on information obtained from the internet or from beauty influencers they follow. However, another impact of this advertising is that illegal cosmetics are also circulating on the market. Therefore, it is necessary to provide assistance so that high school/K students in Karawang Regency understand how to select and use cosmetics safely and understand the impacts of using cosmetics with dangerous chemicals. This activity was carried out using the outreach method using leaflet media. The results of this outreach are expected to increase the understanding of SMA/K students in Karawang Regency regarding cosmetics. Apart from that, SMA/K students in Karawang Regency have knowledge and are wise in choosing and using cosmetics